Larval ascariasis elicits a prominent IgA and IgG1/2 antibody response to adult Ascaris excretory/secretory antigens in pigs - Musimbi, Zaneta D.; Laubschat, Alexandra; Oser, Larissa; Mugo, Robert M.; Hempel, Benjamin-Florian; Höfler, Philipp; Schlosser-Brandenburg, Josephine; Midha, Ankur; Rausch, Sebastian; Hartmann, Susanne (Frontiers in Immunology, 2025)
Roundworm infections result in morbidity, causing significant health and economic concerns in humans and pigs, respectively. We investigated the humoral responses of Ascaris suum infected pigs before and after transition from larval to adult stage and confirmed our previous report on the diagnostic value of human Ascaris-specific antibodies. We evaluated the systemic and mucosal humoral responses in Ascaris infected pigs at 14- and 35-days post-infection (dpi). Ascaris-specific antibodies against larval and adult worm antigens and adult excretory/secretory (ES) products in serum, broncho-alveolar lavage fluid and intestinal mucus were quantified by ELISA. IgA+ B cells in jejunal/ileal mesenteric lymph nodes (mLNs) were investigated using flow cytometry. ES products reliably reported parasite-specific IgM, IgA, IgG and IgG1/2 present in sera at 35 dpi (adult stage) and even at 14 dpi (larval stage). Neither variable worm burdens nor the coinfection with Salmonella affected the ES-specific antibody profiles. Extracts of the third-stage larvae (L3) were less suited but clearly reported L3-specific secretory IgA in lung and intestine. IgA+ B cells expanded in lymph nodes draining jejunum and ileum at day 14 post infection but leveled down to background controls at 35 days after primary infection. A strong correlation between sIgA and eosinophil numbers was seen in the lung, validating previous observations in mice for the definite host. The balanced targeting of L3-somatic antigens and adult ES by sIgA in mucosal sites contrasted with prominent parasite-specific IgA in sera which exclusively reacted to ES products. Collectively, our data indicate extensive antigenic overlap between Ascaris life stages, facilitating the detection of pre-patent and larval stage infection. We further point out distinct mucosal/systemic IgA responses in Ascaris infection which deserve further functional investigations.